Philosophy and citizenship: between affirmation and training - Durán, Maximiliano; Martins, Fabiana Fernandes Ribeiro (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Ethical and citizen education is one of the fundamental pillars of modern Latin American schools. Since the beginning of the nineteenth century, intellectuals and politicians have seen school as a special locus for the social and political formation of their inhabitants. Several authors defend, in different perspectives, that school is a type of citizenship machine. Even though political and institutional changes have taken place in the last two hundred years, we argue that this idea still remains valid. The school understood as a citizenship machine supposes a type of distance between the formed citizen and the one that is not yet formed. This distance is based on a conception of equality as an objective to be achieved. According to this way of conceiving citizenship, children are not equal to educated citizens. In other words, the citizenship which is affirmed by school is that one that has to be formed through the educational process. The question that inspires our work is: who are those we call citizens, those to whom our pedagogical efforts are directed?